Microwave-assisted batch synthesis of Pongamia biodiesel. Issue 6 (November 2010) - Kamath, Venkatesh; Regupathi, I; Saidutta, MB
Background: The major bottleneck of biodiesel synthesis is its cost and this is mainly attributed to the feedstock material. Pongamia pinnata oil is a nonedible oil that is available in plenty in India and has negligible applications. Several methods of synthesis have been established, each having their own advantages and disadvantages.Results & discussion: Biodiesel from high-free fatty acid, nonedible, Pongamia oil was synthesized under microwave irradiation with single- and two-step methods. Experimental investigations showed that although the single-step method had a high yield (80%), the acid value of biodiesel was quite high. Hence, the two-step method seems to be a better approach as it yielded 90%, with 1:10 oil:methanol molar ratio and 1 wt% KOH. Along with a decrease in the reaction time to 4–5 min, separation time was also decreased by at least 90%. A conventional heating method was employed to compare the effects of microwave irradiation on biodiesel synthesis.Conclusion: The results indicate significant improvement in the yield, reaction time and processing time of biodiesel under microwave irradiation. The synthesis of Pongamia biodiesel under microwave irradiation could perhaps lead to cost effective and faster technology in countries such as India.